Diclofenac sodium effects on spontaneous behavioral activity of rats with osteoarthritis and concomitant hypothyroidism - D. S. Nosivets; V. Yo. Mamchur; V. I. Opryshko (Zaporožskij Medicinskij Žurnal)
The aim of the study – to investigate the effect of diclofenac sodium on the spontaneous behavioral activity of rats in conditions of osteoarthritis with concomitant hypothyroidism.